Story of habil and qabil: timeless quran stories - Khan, Saniyasnain (Goodword Books New Delhi, India, 2004)
"Story of Habil and Qabil: Timeless Quran Stories" narrates the tale of the two sons of Adam, focusing on their rivalry and the moral lessons that arise from it. The story illustrates themes of jealousy, sacrifice, and the consequences of one's choices, emphasizing the importance of faith, righteousness, and the value of making good decisions.